2006
DOI: 10.1063/1.2206887
|View full text |Cite
|
Sign up to set email alerts
|

Structural and magnetic properties of Co∕Pt(111) with Ni buffer layers

Abstract: Structural and magnetic properties of a chemically ordered face-centered-cubic (111) Mn alloy filmMagneto-optical Kerr effect, low-energy electron diffraction, and Auger electron spectroscopy were used to investigate the magnetic properties and the growth mode of ultrathin Co films deposited on 1 ML ͑monolayer͒ Ni/ Pt͑111͒ at room temperature. No Kerr signal was observed when the thickness of Co film was below 3 ML, and the easy axis of the magnetization was in plane when the thickness of Co was greater than 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Then Co atoms were deposited on the 1 ML Ni/ Pt(1 1 1). The initial growth of Co films on 1 ML Ni/ Pt(1 1 1) was a 2-ML layer-by-layer mode, after which it turned into a 3-D island growth [10]. AES is a suitable technique to study surface diffusion during the heating process.…”
Section: Resultsmentioning
confidence: 99%
“…Then Co atoms were deposited on the 1 ML Ni/ Pt(1 1 1). The initial growth of Co films on 1 ML Ni/ Pt(1 1 1) was a 2-ML layer-by-layer mode, after which it turned into a 3-D island growth [10]. AES is a suitable technique to study surface diffusion during the heating process.…”
Section: Resultsmentioning
confidence: 99%
“…The growth of 2 MLs of Co on 1 ML of Ni/Pt(111) occurred layer by layer at room temperature. 18) It has been reported that, for as-deposited Co/1 ML Ni/Pt(111) films, neither the polar nor longitudinal Kerr rotations can be observed when the thickness of the Co film is below 3 MLs. The easy axis of magnetization is in the in-plane direction when the thickness of the Co film is greater than 3 MLs.…”
Section: Resultsmentioning
confidence: 99%
“…The easy axis of magnetization is in the in-plane direction when the thickness of the Co film is greater than 3 MLs. 18) To investigate the effects of the Ni buffer layer and the thickness of Co films on the magnetic properties, the evolutions of polar remnant Kerr rotations (M R ) of 2 ML Co/Pt(111), 1 ML Co/1 ML Ni/Pt(111), and 2 ML Co/Pt(111) versus the sample temperature (T S ) after annealing at 750 and 850 K for 20 min are shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 99%